Structure‐activity relationship studies of shortened analogues of the antimicrobial peptide EeCentrocin 1 from the sea urchin Echinus esculentus - Solstad, Runar Gjerp; Johansen, Cecilie; Stensvåg, Klara; Strøm, Morten B.; Haug, Tor (Journal of Peptide Science, 2019)
EeCentrocin 1 is a potent antimicrobial peptide isolated from the marine sea urchin Echinus esculentus . The peptide has a hetero‐dimeric structure with the antimicrobial activity confined in its largest monomer, the heavy chain (HC), encompassing 30 amino acid residues. The aim of the present study was to develop a shorter drug lead peptide using the heavy chain of EeCentrocin 1 as a starting scaffold and to perform a structure‐activity relationship study with sequence modifications to optimize antimicrobial activity. The experiments consisted of 1) truncation of the heavy chain, 2) replacement of amino acids unfavourable for in vitro antimicrobial activity, and 3) an alanine scan experiment on the truncated and modified heavy chain sequence to identify essential residues for antimicrobial activity. The heavy chain of EeCentrocin 1 was truncated to less than half its initial size, retaining most of its original antimicrobial activity. The truncated and optimized lead peptide ( P6 ) consisted of the 12 N ‐terminal amino acid residues from the original EeCentrocin 1 HC sequence and was modified by two amino acid replacements and a C ‐terminal amidation. Results from the alanine scan indicated that the generated lead peptide ( P6 ) contained the optimal sequence for antibacterial activity, in which none of the alanine scan peptides could surpass its antimicrobial activity. The lead peptide ( P6 ) was also superior in antifungal activity compared to the other peptides prepared and showed minimal inhibitory concentrations (MICs) in the low micromolar range. In addition, the lead peptide ( P6 ) displayed minor haemolytic and no cytotoxic activity, making it a promising lead for further antimicrobial drug development.